Helicobacter pylori Chronic Infection Selects for Effective Colonizers of Metaplastic Glands - V. P. O’Brien; L. K. Jackson; J. P. Frick; A. E. Rodriguez Martinez; D. S. Jones; C. D. Johnston; N. R. Salama (mBio, 2023)
ABSTRACT Chronic gastric infection with Helicobacter pylori can lead to progressive tissue changes that culminate in cancer, but how H. pylori adapts to the changing tissue environment during disease development is not fully understood. In a transgenic mouse gastric metaplasia model, we found that strains from unrelated individuals differed in their ability to infect the stomach, to colonize metaplastic glands, and to alter the expression of the metaplasia-associated protein TFF3. H. pylori isolates from different stages of disease from a single individual had differential ability to colonize healthy and metaplastic gastric glands. Exposure to the metaplastic environment selected for high gastric colonization by one of these strains. Complete genome sequencing revealed a unique alteration in the frequency of a variant allele of the putative adhesin sabB, arising from a recombination event with the related sialic acid binding adhesin (SabA) gene. Mutation of sabB in multiple H. pylori strain backgrounds strongly reduced adherence to both normal and metaplastic gastric tissue, and highly attenuated stomach colonization in mice. Thus, the changing gastric environment during disease development promotes bacterial adhesin gene variation associated with enhanced gastric colonization. IMPORTANCE Chronic infection with Helicobacter pylori is the primary risk factor for developing stomach cancer. As disease progresses H. pylori must adapt to a changing host tissue environment that includes induction of new cell fates in the cells that line the stomach. We tested representative H. pylori isolates collected from the same patient during early and later stages of disease in a mouse model where we can rapidly induce disease-associated tissue changes. Only the later-stage H. pylori strains could robustly colonize the diseased stomach environment. We also found that the ability to colonize the diseased stomach was associated with genetic variation in a putative cell surface adhesin gene called sabB. Additional experiments revealed that SabB promotes binding to stomach tissue and is critical for stomach colonization by the late-stage strains. Thus, H. pylori diversifies its genome during disease progression and these genomic changes highlight critical factors for bacterial persistence.